547 Identification of the immune landscape in penile squamous cell carcinoma using multiplex immunofluorescence and spatial image analysis. (9th November 2020) - Segura, Rossana Lazcano; Krishnan, Santhoshi; Oneka, Morgan; Netto, Federico; Lu, Xin; Rao, Priya; Pandurengan, Renganayaki; Pickering, Curtis; Pettaway, Curtis; Chahoud, Jad; Parra, Edwin
Abstract : Background: Penile squamous cell carcinoma (PSCC) is rare in the US accounting for 0.7% of the total cancer incidence. Around 50% of PSCC cases are associated with HPV infection and between 40–60% have high PD-L1 expression. The identification of the immune landscape in PSCC using the spatial proximity between tumor cells and immune phenotypes has not been described yet. Methods: We performed multiplex immunofluorescence (mIF) on 54 formalin-fixed, paraffin-embedded tissue sections of PSCC. The staining was performed with the opal-7 kit (Akoya/PerkinElmer) in the Leica Bond RX autostainer using 7 markers against, Cytokeratins, CD3, CD8, CD68, PD-1, and PD-L1. The slides were scanned in the multispectral microscopy Vectra Polaris (Akoya/PerkinElmer), and 5 regions of interest (ROI) per case were selected and analyzed using the digital image analysis software InForm 2.2.4. The X and Y coordinate from each cell phenotype was obtained from each ROI. Nearest neighbor median distance and the infiltration analysis using the G-function metric of the different tumor associated immune cells (TAICs) within a distance of 20, 40 and 60 microns from the tumor cells were obtained through the R studio software and correlated with available clinical information. Results: Using the nearest neighbor cell analysis we identified the distance of ≤87.33 microns as a close median distance from tumor cells to the multiple TAICs. In our cohort of PSCC tumors, the closest TAIC phenotype to tumor cells was the CD3+ T cells with a median distance of 20.13 microns, followed by macrophages CD68 (median distance, 21.19 microns) and cytotoxic T cells (CD3+, CD8+) with a median distance of 36.09 microns, compared with the others TAICs located farther than 87.33 microns (table 1, figure 1). Interestingly, cytotoxic T cells (median distance, 59.5 micros), T-cells (median distance, 65.6 microns) and macrophages expressing PD-L1 (median distance, 61.2 microns) are located closer to tumor cells expressing PD-L1 than from tumor cells not expressing PD-L1 (median distance, 104.08, 116.05 and 118.74 microns, respectively). Unexpectedly, HPV negative patients had closer cytotoxic T cells CD3+CD8+ median distance, 30.88 microns) and cytotoxic T cells antigen experienced CD3+CD8+PD-1+ (median distance, 50.09 microns), compared to HPV positive patients (median distance of 36.09 and 59.83 microns, respectively). Additionally, the G-function AUC metric from tumor cells to macrophages CD68 showed high interaction at 40 microns in HPV cases when compared with others distances and not HPV cases (P=0.049, figure 2). Conclusions: Although, higher densities of cytotoxic T cells were observed relatively closer from tumor cells than others TAIC subsets, we didn't find strong interaction with this subset in using the G-function AUC metric. The PD-1/PD-L1 axis was also found in close proximity suggesting that there are more likely to interact with tumor cells generating a strongly immunosuppressive microenvironment. In addition, while CD68+ macrophages were found to be closely associated with tumor cells, PD-L1+ macrophages were found to have the closest interaction with tumor cells. The potential of these cell phenotypes to generate a strongly immunosuppressive microenvironment need to be explored in additional cases.